Implementasi Manajemen Operasional di Apotek Farma (di Jl. Chusnan Ali depan MI Tarbiyah Banin Banat, RT/RW: 04/01, Jetak, Kec. Montong, Kab Tuban) - Safika, Fitri Dwi Nur; Adhim, Moh. Agus Dwi Assahrul; Khoiriyah, Arifatul; Marsono (Shofanah Media Berkah, 2026)
This study aims to explore the implementation of operational management at Apotek Farma, located in Montong District, Tuban Regency, and identify obstacles that arise during its implementation. The research method used was field research with a qualitative approach. Informants included responsible pharmacists, technical staff in the pharmaceutical field, and pharmacy employees. The findings indicate that operational management at Apotek Farma has been implemented, but has not yet reached optimal levels in all sectors. Drug inventory management applies the FIFO and FEFO principles, although stock recording remains rudimentary and not fully computerized. Human resource management is considered good, but the number of pharmacy staff is limited during peak hours. To improve service, various improvements have been made to prescription processing procedures, drug counseling, and collaboration with distributors. The main obstacles encountered include delays in drug delivery, the presence of drugs nearing their expiration date, and changes in patient needs.